On natural desire of perfection that makes happy - Maréchal, Joseph; Bańka, Aleksander R.; Surzyn, Jacek (Folia Philosophica, 2011)
The article contains a Polish translation of Joseph Maréchal's text: On the natural desire for happiness-inducing perfection.